A contemporary method for developmental-genetic analyses of age changes in intellectual abilities - McArdle, John J.; Prescott, Carol A.; Hamagami, Fumiaki; Horn, John L. (Developmental neuropsychology, 1998)
The purpose of this article is to describe a methodology for the evaluation of biometric genetic hypotheses in the context of a developmental model of growth and change. Linear structural equation models are described for longitudinal and twin data, including aspects of subject attrition and practice effects. These models are applied to 2 variables measured at several points in time in the New York Twin Study (Jarvik, Kallman, & Falek, 1962; Kallman, Feingold, & Bondy, 1951). The patterns of psychometric and biometric changes are different for the 2 intellectual variables. Substantive results are discussed in relation to g f /g c theory (Cattell, 1971; Horn, 1988), and some methodological limitations are emphasized.